The Potential Tsunami Impact to Coastal Vegetation and Geological Landscape at Teluk Senangin, Lumut, Perak. - bin Rafiuddin, Mohammad Ashraf (Universiti Teknologi PETRONAS, 2016)
The event of a tsunami and its devastating impact is no longer a bizarre occurrence to the world. Many researches and studies have been conducted and is still being conducted to understand the cause of this event and to find a way to predict potential tsunamis around the world. Malaysia has been known to be affected by tsunamis. This study aims to analyze the impact of a potential tsunami on the coast of Perak with the aids of wave simulation models. Earthquakes that occur in the sea are the primary reason for tsunami. The greater the magnitude and the shallower the focus point of the quake, the greater the impact of the tsunami. By using a software called TUNA-M2, a wave simulation model can be constructed to predict the impact of a potential tsunami at the study area. Based on this model, the time taken for the tsunami to reach the study area, the direction and speed of wave propagation, the wave run-up and the inundation of the tsunami can all be predicted. It was found in this study that a tsunami of significant impact, greater than the 2004 tsunami, is able to affect the area. Based on the simulation, the inundation distance was estimated to be about 70-80m from the shoreline. It is hoped that through this paper, many more detailed researches regarding earthquake and tsunami can be carried out. It is also an aim that this paper brings about developing earthquake and tsunami resilient societies worldwide.